Prepreg, fiber-reinforced composite material, tubular body made of fiber-reinforced composite material, golf club shaft, and fishing rod
By using technical means of using specific resin compositions and fiber-reinforced composite materials, the shortcomings of existing materials in terms of mechanical properties, heat resistance, transparency and weather resistance are solved, and excellent performance in applications such as golf club shafts and fishing rods are achieved.
Patent Information
- Application Number
- CN202380053408.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-02
- Filing Date
- 2023-06-27
- Publication Date
- 2025-02-28
AI Technical Summary
In the application of golf club shafts, fishing rods, etc., it is difficult to achieve excellent mechanical characteristics, heat resistance, transparency and weather resistance at the same time.
A resin composition containing novolac type epoxy resin, zolidinone type epoxy resin, sorbitol type epoxy resin and dicyandiamide is used as a prepreg, and a fiber reinforced composite material with excellent properties is formed by adjusting the proportion of each component and adding a phenoxy resin and a curing promoter.
It has achieved excellent elastic modulus and heat resistance of fiber-reinforced composite materials, and has good transparency and weather resistance, and is suitable for golf club shafts, fishing rods and other applications.
Smart Images

Figure CN119546679A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a fiber-reinforced composite material suitable for aerospace applications, general industrial applications, sports applications, etc., a prepreg, a fiber-reinforced composite material, a tubular body made of a fiber-reinforced composite material, and further relates to a golf club shaft and a fishing rod made of the tubular body made of the fiber-reinforced composite material. Background Art
[0002] Fiber-reinforced composite materials using carbon fiber, aramid fiber, etc. as reinforcing fibers are widely used in structural materials of aircraft, automobiles, etc., sports and general industrial uses such as tennis rackets, golf club shafts, fishing rods, bicycles, and shells, etc., due to their high specific strength and specific elastic modulus. As the resin composition used for the fiber-reinforced composite material, thermosetting resins are mainly used from the viewpoints of heat resistance and productivity, and epoxy resins are preferably used from the viewpoint of mechanical properties such as adhesion to the reinforcing fibers.
[0003] In recent years, when fiber-reinforced composite materials are applied to golf club shafts, fishing rods, bicycles and other applications that require further lightweight, various physical properties have been required to be improved. For example, in order to show excellent bending strength in tubular bodies such as golf club shafts and fishing rods, the fiber-reinforced composite materials used require high fiber direction strength and non-fiber direction strength, which are greatly affected by the strength and elastic modulus of the epoxy resin itself used as the matrix resin. In addition, when the fiber-reinforced composite materials are processed into final products, high heat resistance that can withstand processing heat is also required. Furthermore, the situation of using cross-eyes (cross mesh) of reinforcing fibers as designs by transparently coating the surface of the fiber-reinforced composite materials has also increased. Therefore, in the epoxy resin used as the matrix resin, in addition to the excellent mechanical properties and heat resistance of the cured product, the appearance of the cured product such as weather resistance and transparency is also valued.
[0004] In Patent Document 1, a method of combining mechanical properties with heat resistance is studied. The invention discloses a prepreg having an excellent appearance of a fiber-reinforced composite material by mixing an oxazolidinone epoxy resin with a novolac epoxy resin. In addition, in Patent Document 2, a prepreg having excellent appearance of a fiber-reinforced composite material without turbidity caused by moisture absorption is studied by using an epoxy resin composition having a parallel light transmittance of 30% or more. Furthermore, in Patent Document 3, a tow prepreg having excellent breaking strain and transparency of a resin composition by mixing a dissolution accelerator such as a sorbitol epoxy resin in order to reduce the situation where the dicyandiamide used as a curing agent is dissolved and remains and becomes a defect is studied.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2020 / 080474
[0008] Patent Document 2: Japanese Patent Application Publication No. 2003-261744
[0009] Patent Document 3: Japanese Patent Application Publication No. 2020-158594 Summary of the invention
[0010] Problems to be solved by the invention
[0011] When the technology of Patent Document 1 is used, although elastic modulus and heat resistance can be achieved, no consideration is given to appearance such as weather resistance and transparency, and an excellent appearance cannot be stably obtained. In addition, when the technology of Patent Document 2 is used, although a resin cured product with excellent transparency and a molded product without turbidity caused by moisture absorption are obtained, the elastic modulus of the resin cured product is low, and excellent mechanical properties may not be obtained in a fiber-reinforced composite material. Furthermore, in Patent Document 2, no consideration is given to weather resistance, and there is room for improvement in weather resistance. In Patent Document 3, although a resin cured product with excellent transparency is obtained, the elastic modulus and heat resistance of the resin cured product are low, and excellent mechanical properties and heat resistance may not be obtained in a fiber-reinforced composite material. In addition, regarding Patent Document 3, no consideration is given to weather resistance, and excellent weather resistance cannot be stably obtained.
[0012] Therefore, the present invention aims to provide a prepreg formed from a resin composition which is excellent in elastic modulus and heat resistance and also excellent in appearance such as weather resistance and transparency, and a fiber-reinforced composite material using the prepreg, which is excellent in mechanical properties, heat resistance and appearance, a fiber-reinforced composite material tubular body, a golf club shaft, and a fishing rod.
[0013] Means for solving problems
[0014] 1. A prepreg comprising reinforcing fibers and a resin composition, wherein the resin composition comprises the following components [A] to [D] and satisfies the following conditions (1) to (5).
[0015] Component [A]: Novolac type epoxy resin
[0016] Ingredient [B]: Oxazolidinone epoxy resin
[0017] Component [C]: either or both of sorbitol-based epoxy resin and glycerin-based epoxy resin
[0018] Ingredient [D]: Dicyandiamide
[0019] Condition (1): The content of the component [A] is 20 to 50 parts by mass based on 100 parts by mass of all epoxy resins.
[0020] Condition (2): The content of the component [B] is 10 to 40 parts by mass based on 100 parts by mass of all epoxy resins.
[0021] Condition (3): The content of the component [C] is 10 to 40 parts by mass based on 100 parts by mass of all epoxy resins.
[0022] Condition (4): The total amount of component [B] and component [C] is 40 parts by mass or more in 100 parts by mass of the total epoxy resin.
[0023] Condition (5): Component [E]: glycidylamine epoxy resin is not contained, or even if contained, the content is 10 parts by mass or less based on 100 parts by mass of the total epoxy resin.
[0024] 2. The prepreg according to item 1 above, which does not contain the component [E], or even if it contains it, the amount is 1 part by mass or less based on 100 parts by mass of the total epoxy resin.
[0025] 3. The prepreg according to 1 or 2 above, comprising component [F]: a compound having a boiling point of 130° C. or higher, a molecular weight m of 50 to 250, no epoxy group in the molecule, and no epoxy resin curing ability.
[0026] 4. The prepreg according to any one of 1 to 3 above, comprising component [G]: a phenoxy resin as the thermoplastic resin.
[0027] 5. A fiber-reinforced composite material obtained by curing the prepreg according to any one of 1 to 4 above.
[0028] 6. A fiber-reinforced composite material tubular body obtained by molding the prepreg according to any one of 1 to 4 above.
[0029] 7. A golf club shaft, which is formed by using the fiber-reinforced composite material tubular body described in 6 above.
[0030] 8. A fishing rod, which is made of a tubular body made of the fiber-reinforced composite material according to 6 above.
[0031] Effects of the Invention
[0032] According to the present invention, a prepreg formed from a resin composition having excellent elastic modulus and heat resistance and also excellent appearance such as weather resistance and transparency, as well as a fiber-reinforced composite material using the prepreg, having excellent mechanical properties, heat resistance and appearance, a fiber-reinforced composite material tubular body, a golf club shaft, and a fishing rod can be obtained. DETAILED DESCRIPTION
[0033] Hereinafter, the present invention will be described in detail.
[0034] The prepreg of the present invention comprises a resin composition and reinforcing fibers. Preferably, the prepreg comprises a resin composition and reinforcing fibers. The resin composition comprises components [A] to [D] as essential components.
[0035] Component [A] in the present invention is a novolac epoxy resin. By including component [A], the elastic modulus and heat resistance of the cured resin are improved without impairing weather resistance, thereby obtaining a fiber-reinforced composite material having excellent mechanical properties, heat resistance and appearance.
[0036] It is necessary to include 20 to 50 parts by mass of component [A] relative to 100 parts by mass of all epoxy resins contained in the resin composition. As for the lower limit, it is preferably 25 parts by mass or more, and more preferably 30 parts by mass or more. As for the upper limit, it is preferably 45 parts by mass or less, and more preferably 40 parts by mass or less. By including component [A] in this range, the transparency of the cured resin is excellent, and the balance of mechanical properties, heat resistance, and appearance becomes good.
[0037] In order to achieve a good balance between the bending modulus and heat resistance of the cured resin, the lower limit of the softening point of the novolac epoxy resin is preferably 50°C or higher, more preferably 60°C or higher. The upper limit of the softening point is preferably 120°C or lower, more preferably 110°C or lower.
[0038] As component [A], phenol novolac type epoxy resin and cresol novolac type epoxy resin are mentioned.
[0039] Commercially available products of phenol novolac type epoxy resins include "jER (registered trademark)" 152, 154 (above, manufactured by Mitsubishi Chemical Co., Ltd.), EPPN-201 (manufactured by Nippon Kayaku Co., Ltd.), "EPICLON (registered trademark)" N-740, N-770 (softening point: 70°C), N-775 (softening point: 75°C, above, manufactured by DIC Corporation), etc.
[0040] Commercially available products of cresol novolac type epoxy resins include "EPICLON (registered trademark)" N-660 (softening point: 66°C), N-665 (softening point: 70°C), N-670 (softening point: 73°C), N-673 (softening point: 78°C), N-680 (softening point: 87°C), N-690 (softening point: 93°C), N-695 (softening point: 95°C or above, manufactured by DIC Corporation), etc.
[0041] The component [B] in the present invention is Oxazolidone type epoxy resin. By including component [B], the heat resistance of the cured resin can be improved without impairing the weather resistance. In addition, by including component [B], the dissolution of dicyandiamide as component [D] can be promoted, thereby improving the transparency of the cured resin. That is, by including component [B], a fiber-reinforced composite material having excellent heat resistance and appearance can be obtained.
[0042] It is necessary to include 10 to 40 parts by mass of component [B] relative to 100 parts by mass of all epoxy resins contained in the resin composition. As for the lower limit, it is preferably 15 parts by mass or more, and more preferably 20 parts by mass or more. As for the upper limit, it is preferably 35 parts by mass or less, and more preferably 30 parts by mass or less. If the content of component [B] is above the above lower limit, the heat resistance and transparency of the cured resin are excellent, and if it is below the above upper limit, the bending modulus of the cured resin is not impaired. That is, by including component [B] in this range, the balance of transparency, heat resistance and bending modulus of the cured resin becomes good.
[0043] As commercially available products of component [B], AER4152, AER4151 (manufactured by Asahi Kasei Instruments Co., Ltd.), "DER (registered trademark)" 852, 858 (manufactured by Dai Chemical Co., Ltd.), TSR-400 (manufactured by DIC Corporation), ACR1348 (manufactured by Adeka Corporation) and the like can be used.
[0044] Component [C] in the present invention is either or both of a sorbitol-type epoxy resin and a glycerol-type epoxy resin. It should be noted that, when both a sorbitol-type epoxy resin and a glycerol-type epoxy resin are included, they are combined to form component [C]. They can be used alone or in combination. By including component [C], the bending modulus of the cured resin can be increased without damaging the weather resistance. In addition, component [C] has a high polarity due to the presence of a hydroxyl group in the molecular structure, which promotes the dissolution of dicyandiamide as component [D], thereby improving the transparency of the cured resin. That is, by including component [C], a fiber-reinforced composite material having excellent bending modulus and appearance is obtained.
[0045] It is necessary to include 10 to 40 parts by mass of component [C] relative to 100 parts by mass of all epoxy resins contained in the resin composition. As for the lower limit, it is preferably 15 parts by mass or more, and more preferably 20 parts by mass or more. As for the upper limit, it is preferably 35 parts by mass or less, and more preferably 30 parts by mass or less. If the content of component [C] is above the above lower limit, the bending modulus and transparency of the resin cured product are excellent, and if it is below the above upper limit, the heat resistance of the resin cured product is not impaired. That is, by including component [C] in this range, the balance of transparency, heat resistance and bending modulus of the resin cured product becomes good.
[0046] Examples of the glycerin-type epoxy resin of component [C] include monoglycerin-type epoxy resins, diglycerin-type epoxy resins, and polyglycerin-type epoxy resins.
[0047] Examples of commercially available products of the sorbitol-based epoxy resin include "Denacol (registered trademark)" EX-612, EX-614, EX-614B, and EX-622 (all manufactured by Nagase Chemtex Co., Ltd.).
[0048] Commercially available products of glycerol epoxy resins include "Denacol (registered trademark)" EX-313 and EX-314 (manufactured by Nagase Chem Tech Co., Ltd.). Commercially available products of diglycerol epoxy resins include "Denacol (registered trademark)" EX-421 (manufactured by Nagase Chem Tech Co., Ltd.). Commercially available products of polyglycerol epoxy resins include "Denacol (registered trademark)" EX-512 and EX-521 (manufactured by Nagase Chem Tech Co., Ltd.).
[0049] As condition (4) in the present invention, it is required that the total content of component [B] and component [C] is 40 parts by mass or more relative to 100 parts by mass of the total epoxy resin. As for the lower limit, it is preferably 45 parts by mass or more, and more preferably 50 parts by mass or more. In addition, as for the upper limit, the total of the upper limits of the individual components in conditions (2) and (3) is 80 parts by mass or less, but preferably 70 parts by mass or less, and more preferably 60 parts by mass or less. By making the total content of component [B] and component [C] relative to 100 parts by mass of the total epoxy resin within the above range, the transparency of the cured resin is significantly improved, and a fiber-reinforced composite material having an excellent appearance (white turbidity is improved) is obtained.
[0050] As the condition (5) in the present invention, it is necessary not to contain the glycidylamine type epoxy resin as component [E], or even if contained, it is 10 parts by mass or less relative to 100 parts by mass of the total epoxy resin. In addition, even if component [E] is contained, it is more preferably 5 parts by mass or less, and further preferably 1 part by mass or less. By making the compounding amount of component [E] 10 parts by mass or less, the improvement of the weather resistance of the cured resin is not hindered, and a fiber-reinforced composite material with excellent weather resistance is obtained.
[0051] Examples of the glycidylamine epoxy resin as component [E] include glycidylamine epoxy resins having an aromatic ring and aliphatic glycidylamine epoxy resins, and examples thereof include diaminodiphenylmethane epoxy resins, diaminodiphenylsulfone epoxy resins, aminophenol epoxy resins, meta-xylylenediamine epoxy resins, and 1,3-bisaminomethylcyclohexane epoxy resins.
[0052] Examples of commercially available diaminodiphenylmethane-type epoxy resins include ELM434 (manufactured by Sumitomo Chemical Co., Ltd.), "Araldos (registered trademark)" MY720, MY721, MY9512, and MY9663 (above, "Alarac"). Manufactured by ン・アドバンスト・マテリアルズ Co., Ltd.), "エポトート (registered trademark)" YH-434 (Japanese Railways Made by Mitsubishi Microelectronics Co., Ltd.), "jER (registered trademark)" 604 (manufactured by Mitsubishi Microelectronics Co., Ltd.), etc.
[0053] Examples of commercially available products of diaminodiphenyl sulfone epoxy resins include TG3DAS (manufactured by Mitsui Chemicals, Inc.).
[0054] Commercially available products of aminophenol-type epoxy resins include ELM120, ELM100 (manufactured by Sumitomo Chemical Co., Ltd.), "jER (registered trademark)" 630 (manufactured by Mitsubishi Chemical Corporation), and "Aldair (registered trademark)" MY0500, MY0510, MY0600, and MY0610 (manufactured by Handman Advanced Materials Co., Ltd.).
[0055] Examples of commercially available products of the meta-xylylenediamine epoxy resin include "TETRAD (registered trademark)"-X (manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0056] Examples of commercially available products of 1,3-bisaminomethylcyclohexane-based epoxy resins include "TETRAD (registered trademark)"-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0057] The resin composition used in the present invention may be appropriately blended with epoxy resins other than those mentioned above within a range that does not impair the effects of the present invention. Specifically, epoxy resins of bisphenol type, isocyanuric acid type, dicyclopentadiene type, hydantoin type, trimethylolpropane type, pentaerythritol type, trihydroxyphenylmethane type and tetraphenolylethane type may be mentioned.
[0058] Among them, commercially available products of bisphenol A type epoxy resins include "jER (registered trademark)" 825, 828, 834, 1001, 1002, 1003, 1003F, 1004, 1004AF, 1005F, 1006FS, 1007, 1009, and 1010 (manufactured by Mitsubishi Chemical Corporation), "Epiclon (registered trademark)" 850 (manufactured by DIC Corporation), "Epot (registered trademark)" YD-128 (manufactured by Nippon Tetsu Chemical & Material Corporation), and "DER (registered trademark)" -331 and 332 (manufactured by Daw Chemical Corporation).
[0059] Examples of commercially available bisphenol F-type epoxy resins include "Aralapton (registered trademark)" GY282 Manufactured by ドバンスト・マテリアルズ Co., Ltd.), "jER (registered trademark)" 806, 807, 4005P, 400 7P, 4010P (above, manufactured by Mitsubishi Micron Co., Ltd.), "EPICLON (registered trademark)" 830 (DI C Co., Ltd.) and "Etotron (registered trademark)" YD-170 (manufactured by Nippon Iron & Steel Co., Ltd.), etc.
[0060] Component [D] in the present invention is dicyandiamide. Dicyandiamide is excellent in giving epoxy resin cured products high mechanical properties and heat resistance, and is widely used as a curing agent for various epoxy resins. In addition, it can be suitably used in view of the excellent weather resistance and storage stability of epoxy resin compositions. Examples of commercially available products of such dicyandiamide include DICY7 and DICY15 (all manufactured by Mitsubishi Chemical Co., Ltd.).
[0061] In addition, in the present invention, from the perspective of excellent balance among mechanical properties, heat resistance and transparency of the cured resin, the content of component [D] is preferably 4 to 12 parts by mass relative to 100 parts by mass of the total epoxy resin. The lower limit is more preferably 5 parts by mass or more, and the upper limit is more preferably 10 parts by mass or less.
[0062] From the viewpoint of controlling the viscosity of the resin composition and the tackiness of the prepreg, the resin composition used in the prepreg of the present invention preferably contains a phenoxy resin as component [G]. Since the phenoxy resin can improve the viscosity of the resin composition and the tackiness of the prepreg without impairing the weather resistance of the cured resin, it is preferably mixed in order to produce a prepreg with excellent workability.
[0063] Examples of commercially available phenoxy resins include "Fennotot (registered trademark)" YP-50, YP-50S, and YP-70 (all manufactured by Nippon Tetsu Chemical & Material Co., Ltd.).
[0064] The resin composition used in the prepreg of the present invention may be mixed with a curing accelerator from the viewpoint of controlling the curing rate. Examples of the curing accelerator include urea compounds and imidazole compounds, and urea compounds are particularly preferably used from the viewpoint of the storage stability of the resin composition.
[0065] Examples of urea compounds include 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, phenyldimethylurea, toluenebisdimethylurea, etc. In addition, commercially available aromatic urea compounds include DCMU99 (manufactured by Hodogaya Chemical Industries, Ltd.) and Omicure (registered trademark) 24 (manufactured by Pitti Ijapan Co., Ltd.).
[0066] In view of the fact that the elastic modulus of the cured resin increases, the resin composition used in the present invention preferably contains as component [F] a compound having a boiling point of 130°C or higher, a molecular weight m of 50 or higher and 250 or lower, no epoxy group in the molecule, and no epoxy resin curing ability. Here, compounds such as amines that can undergo addition reaction with epoxy resins, phenols, acid anhydrides that can copolymerize with epoxy resins, imidazoles that can serve as self-polymerization initiators for epoxy resins, aromatic urea compounds, and tertiary amine compounds are compounds that have epoxy resin curing ability and are not included in component [F]. It should be noted that, here, the so-called "no epoxy resin curing ability" refers to the property of not chemically reacting with epoxy resins and not participating in the self-polymerization of epoxy resins.
[0067] It is believed that the component [F] is not introduced into the cross-linked structure formed by the reaction of the epoxy resin and dicyandiamide, but exists in the gaps thereof, and this state is maintained even after the epoxy resin is cured, and thus, it is believed that the elastic modulus of the obtained cured resin is increased. In addition, surprisingly, by mixing the above-mentioned component [F], a cured resin having not only a high elastic modulus but also a high elongation and a high strength is obtained.
[0068] In addition, by making the boiling point of component [F] above 130°C, more preferably above 180°C, it is possible to suppress the volatilization of component [F] during the curing of the resin composition, thereby obtaining a cured resin and a fiber-reinforced composite material having excellent mechanical properties. In addition, by making the boiling point of component [F] within such a range, it is possible to suppress the generation of voids in the obtained fiber-reinforced composite material and the reduction of mechanical properties, which is therefore preferred. In addition, there is no particular upper limit on the boiling point of component [F], but the boiling point of the compound commonly used in the present invention is mostly below 400°C.
[0069] The component [F] is preferably contained in an amount of 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, and more preferably 3 to 6 parts by mass, based on 100 parts by mass of all epoxy resins.
[0070] The molecular weight m of component [F] is 50 to 250, more preferably 70 to 120. By setting the molecular weight of component [F] to be within such a range, component [F] is appropriately held in the voids of the crosslinked structure formed by the reaction of the epoxy resin and dicyandiamide, and a cured product having excellent elastic modulus, strength, and elongation is obtained.
[0071] In the present invention, component [F] is preferably a compound having at least one functional group selected from an amide group, a ketone group, and a hydroxyl group in the molecule. When component [F] has a highly polar functional group as described above in the molecule, a strong intermolecular interaction between the hydroxyl group in the cross-linked structure formed by the epoxy resin and dicyandiamide and component [F] acts, and component [F] is easily properly retained in the voids of the cross-linked structure, thereby obtaining a particularly excellent effect of improving elongation and strength. In addition, when component [F] has a highly polar functional group as described above, the dissolution of dicyandiamide as component [D] can be promoted, thereby improving the transparency of the cured resin.
[0072] Examples of such component [F] include amides such as N-methylformamide, N-methylacetamide, 2-pyrrolidone, N-methylpropionamide, N-ethylacetamide, N-methylacetanilide, and N,N'-diphenylacetamide, and glycols such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, and heptanediol. These compounds may be used alone or in combination.
[0073] As the reinforcing fiber used in the prepreg and fiber reinforced composite material of the present invention, carbon fiber, graphite fiber, aramid fiber, glass fiber, etc. can be preferably cited, and carbon fiber is particularly preferred. There is no limitation on the form and arrangement of the reinforcing fiber, and for example, fiber structures such as long fibers, single short hemp scraps, woven fabrics, knitted fabrics, and braids that are paralleled in one direction are used. As the reinforcing fiber, two or more carbon fibers, glass fibers, aramid fibers, boron fibers, PBO fibers, high-strength polyethylene fibers, alumina fibers, and silicon carbide fibers can be used in combination.
[0074] Specific examples of the carbon fiber include acrylic, pitch, and rayon carbon fibers, and acrylic carbon fibers having high tensile strength are particularly preferably used.
[0075] As the form of carbon fiber, twisted yarn, untwisted yarn and untwisted yarn can be used. In the case of twisted yarn, the orientation of the filaments constituting the carbon fiber is not parallel, which becomes a cause of reduced mechanical properties of the obtained carbon fiber reinforced composite material. Therefore, it is preferred to use untwisted yarn or untwisted yarn that has a good balance between the formability and strength characteristics of the carbon fiber reinforced composite material.
[0076] The tensile modulus of carbon fiber is preferably in the range of 200 to 440 GPa. The tensile modulus of carbon fiber is affected by the crystallinity of the graphite structure constituting the carbon fiber, and the higher the crystallinity, the higher the elastic modulus. If it is in this range, the rigidity and strength of the carbon fiber reinforced composite material are all balanced at a high level, so it is preferred. A more preferred elastic modulus is in the range of 230 to 400 GPa, and more preferably in the range of 260 to 370 GPa. Here, the tensile modulus of carbon fiber is a value measured in accordance with JIS R7601 (2006).
[0077] The prepreg of the present invention can be produced by various known methods. For example, the prepreg can be produced by a hot melt method in which a resin composition is heated to reduce viscosity and then impregnated into reinforcing fibers without using an organic solvent.
[0078] For the hot melt method, the following methods can be used: a method in which the resin composition which has been reduced in viscosity by heating is directly impregnated into the reinforcing fibers; or a method in which the resin composition is first temporarily coated on a release paper or the like with a resin film on a release paper sheet, and then the resin film is overlapped with the reinforcing fiber side from both sides or one side of the reinforcing fiber, and the resin composition is impregnated into the reinforcing fiber by heating and pressurizing.
[0079] The content of reinforcing fibers in the prepreg is preferably 30 to 90% by mass, more preferably 35 to 85% by mass, and further preferably 65 to 85% by mass. If the fiber mass content is small, the amount of resin is too much, and it is not easy to obtain the advantages of fiber-reinforced composite materials with excellent specific strength and specific elastic modulus. In addition, when the fiber-reinforced composite material is formed, the heat release during curing sometimes becomes too high. On the other hand, if the fiber mass content is too large, the impregnation of the resin is poor, and the resulting composite material may become a material with many voids. In addition, the viscosity of the prepreg may be impaired.
[0080] The fiber-reinforced composite material or the fiber-reinforced composite material tubular body of the present invention can be manufactured by laminating the prepreg of the present invention in a predetermined form and applying pressure / heat to cure the resin as an example. Among the methods of applying heat and pressure, press molding, autoclave molding, bag molding, wrapping tape method, internal pressure molding, etc. are used.
[0081] In the molding method of the tubular body made of fiber reinforced composite material, the winding tape method is particularly preferably used. The winding tape method is a method of winding a prepreg around a core bone such as a mandrel to obtain a cylindrical molded body. Specifically, the method is to wind the prepreg around the mandrel, and in order to fix and apply pressure to the prepreg, a winding tape composed of a thermoplastic resin film is wound around the periphery thereof, and after the resin is heated and cured in an oven, the core bone is removed to obtain a cylindrical molded body. This method is suitable for making a tubular body such as a golf club shaft, a fishing rod, etc.
[0082] When the resin composition of the present invention is used, its cured product has excellent mechanical properties, weather resistance, and transparency. Therefore, the fiber-reinforced composite material tubular body of the present invention exhibits excellent flexural strength, weather resistance, and appearance.
[0083] The fiber-reinforced composite material or the fiber-reinforced composite tubular body of the present invention can be widely used for aerospace applications, general industrial applications, and sports applications. More specifically, in general industrial applications, it is suitable for use in structures such as automobiles, ships, and railway vehicles. In sports applications, it is suitable for use in golf club shafts, fishing rods, tennis rackets, and badminton rackets. Among them, the fiber-reinforced composite tubular body of the present invention can be suitable for use in golf club shafts and fishing rods.
[0084] The upper limit and the lower limit of the numerical range described above can be arbitrarily combined unless otherwise specified.
[0085] Example
[0086] Hereinafter, the present invention will be described in detail by way of examples. However, the scope of the present invention is not limited to these examples and is to be interpreted. It should be noted that the unit "part" of the composition ratio refers to parts by mass unless otherwise noted. In addition, the determination of various characteristics (physical properties) was carried out at a temperature of 23° C. and a relative humidity of 50% unless otherwise noted. In addition, the units of the amounts of the various components in the table are all parts by mass.
[0087] <Materials used in Examples and Comparative Examples>
[0088] (1) Reinforcement Fiber
[0089] "Toreka (registered trademark)" T1100G-24K (number of fibers: 24,000, tensile modulus: 324 GPa, density: 1.8 g / cm 3 , manufactured by Tora Co., Ltd.)
[0090] (2) Epoxy resin
[0091] Component [A]: Novolac type epoxy resin
[0092] [A]-1 "EPICLON (registered trademark)" N-775 (phenol novolac type epoxy resin, epoxy equivalent: 189, manufactured by DIC Corporation)
[0093] [A]-2 "EPICLON (registered trademark)" N-695 (cresol novolac type epoxy resin, epoxy equivalent: 214, manufactured by DIC Corporation)
[0094] Component [B]: Oxazolidinone epoxy resin
[0095] [B]-1 "DER (registered trademark)" 858 (epoxy equivalent: 400, manufactured by Dai Chemical Co., Ltd.)
[0096] Component [C]: Sorbitol type epoxy resin, glycerin type epoxy resin
[0097] [C]-1 "Denacol (registered trademark)" EX-614B (sorbitol type epoxy resin, epoxy equivalent: 173, manufactured by Naga Sechem Textiles Co., Ltd.)
[0098] [C]-2 "Denacol (registered trademark)" EX-512 (polyglycerol type epoxy resin, epoxy equivalent: 168, manufactured by Nagase Chemtex Co., Ltd.)
[0099] Component [E]: Glycidylamine type epoxy resin
[0100] [E]-1 "Araloid (registered trademark)" MY0600 (aminophenol type epoxy resin, epoxy equivalent: 118, manufactured by Tornado Co., Ltd.)
[0101] Component [H]: Other epoxy resin
[0102] [H]-1 "EPICLON (registered trademark)" 830 (bisphenol F type epoxy resin, epoxy equivalent: 172, manufactured by DIC Corporation)
[0103] [H]-2 "Denacol (registered trademark)" EX-411 (pentaerythritol type epoxy resin, epoxy equivalent: 229, manufactured by Naga Sechem Textiles Co., Ltd.)
[0104] (3) Component [D]: dicyandiamide
[0105] [D]-1 DICY7 (dicyandiamide, manufactured by Mitsubishi Microwave Co., Ltd.)
[0106] (4) Component [F]: a compound having a boiling point of 130° C. or higher, a molecular weight m of 50 or higher and 250 or lower, having no epoxy group in the molecule, and having no epoxy resin curing ability
[0107] [F]-1 2-Pyrrolidone (boiling point: 245°C, molecular weight m: 85, manufactured by Tokyo Chemical Industry Co., Ltd.)
[0108] [F]-2 1,2-Propanediol (boiling point: 188°C, molecular weight m: 76, manufactured by Tokyo Chemical Industry Co., Ltd.)
[0109] (5) Component [G]: phenoxy resin
[0110] [G]-1 "Fukuro Toro (registered trademark)" YP-70 (manufactured by Nippon Iron & Steel Co., Ltd.)
[0111] (6) Curing accelerator
[0112] DCMU99 (3-(3,4-dichlorophenyl)-1,1-dimethylurea, manufactured by Hodogaya Chemical Industry Co., Ltd.).
[0113] <Method for preparing resin composition>
[0114] (1) Preparation of curing agent masterbatch
[0115] 10 parts by mass of epoxy resin ([C]-1, [C]-2, [H]-1, [H]-2 are equivalent thereto) which is liquid at room temperature (10 parts by mass relative to 100 parts by mass of the total epoxy resin) were prepared. Dicyandiamide as component [D] was added thereto respectively, and kneaded at room temperature. The mixture was passed through a three-roll mill twice to prepare a curing agent masterbatch.
[0116] (2) Preparation of resin composition
[0117] 90 parts by weight of all epoxy resins except 10 parts by weight of liquid epoxy resin used in (1) above are placed in a beaker. While kneading, the temperature is raised to 150°C, and then component [G]: phenoxy resin is added, and heated and kneaded at 150°C for 1 hour to dissolve it. Then, while continuing to knead, the temperature is lowered to 55-65°C, and the curing agent masterbatch prepared in (1) above, component [F] with the components and amounts shown in the table, and a curing accelerator are added, and kneaded at the same temperature for 30 minutes to obtain a resin composition. The composition of each embodiment and comparative example is shown in Tables 1 to 5.
[0118] <Method for producing cured resin>
[0119] The resin composition prepared according to the above-mentioned <Preparation method of resin composition> was degassed in vacuum, and then heated from 30°C at a rate of 1.7°C / min in a mold set so as to have a thickness of 2 mm through a 2 mm thick "Teflon (registered trademark)" spacer. After the temperature reached 90°C and was maintained for 1 hour, the temperature was raised at a rate of 2.0°C / min, and after the temperature reached 135°C, it was cured for 2 hours to obtain a plate-shaped resin cured product with a thickness of 2 mm.
[0120] In the appearance evaluation, the curing reaction was conducted in a mold set to have a thickness of 1 mm with a 1 mm thick "Teflon (registered trademark)" spacer, to obtain a plate-shaped resin cured product having a thickness of 1 mm.
[0121] <Prepreg production method>
[0122] The resin composition prepared according to the above-mentioned <Preparation method of resin composition> was coated on release paper using a knife coater to prepare a resin sheet with a basis weight of 31 g / m 2 Next, the fiber weight is 125 g / m 2The above-mentioned resin film is overlapped on both sides of the reinforcing fibers (the above-mentioned "トレカ (registered trademark)" T1100G-24K) arranged in one direction in a sheet-like manner, and the resin composition is impregnated under heating and pressure under the conditions of a temperature of 110°C and a maximum pressure of 2 MPa to obtain a prepreg.
[0123] <Various evaluation methods>
[0124] (1) Three-point bending measurement of cured resin
[0125] A test piece with a width of 10 mm and a length of 60 mm was cut out from a resin cured product with a thickness of 2 mm produced according to the above-mentioned <Method for producing a resin cured product>, and a three-point bending test was performed using an Instron universal testing machine (manufactured by Instron Co., Ltd.) with a span of 32 mm, a crosshead speed of 2.5 mm / min, and a sample number n=6. The average values of the elastic moduli at this time were set as the bending elastic moduli of the resin cured product.
[0126] (2) Determination of glass transition temperature of cured resin
[0127] From the 2 mm thick resin cured product prepared according to the above <Preparation method of cured resin>, a test piece with a width of 12.7 mm and a length of 55 mm was cut out. For this test piece, a viscoelasticity measuring device (ARES, manufactured by Thei Instruments Co., Ltd.) was used to perform DMA measurement in a temperature range of 40 to 250 ° C under the conditions of a torsional vibration frequency of 1.0 Hz and a heating rate of 5.0 ° C / min, and the glass transition temperature was read. The glass transition temperature is set to the temperature at the intersection of the tangent in the glass state and the tangent in the transition state in the storage elastic modulus G' curve.
[0128] (3) Transparency evaluation of cured resin
[0129] A 1 mm thick cured resin produced according to the above <Preparation method of cured resin> was placed on a paper with written text, and a person having a visual acuity of about 1.0 measured using a Langer ring confirmed the transparency of the cured resin. A case where the text could be clearly read as before the cured resin was placed was expressed as A, a case where the text could be read although blurred was expressed as B, and a case where the text could not be read was expressed as C.
[0130] (4) Weathering test of cured resin
[0131] A test piece with a width of 37 mm and a length of 68 mm was cut out from the 1 mm thick resin cured product prepared according to the above <Preparation method of cured resin>. The test piece was subjected to an accelerated weathering test at a strength of 180 W / m using a Super Weathering Tester (SX-75, manufactured by Suga Testing Machine Co., Ltd.). 2 , black plate temperature 63 ° C, humidity 50% RH, irradiation without water spray for 102 minutes, and intensity 180W / m 2 The weather resistance test was conducted by performing irradiation with water spray for 18 minutes under the conditions of a tank temperature of 28° C. and a humidity of 99% RH, and repeating this cycle 12 times (i.e., 24 hours) as one cycle.
[0132] Weather resistance was evaluated by measuring the color difference (ΔE) of the cured product before and after the weather resistance test using a multi-light source spectrophotometer MSC-P (manufactured by Suga Testing Instruments Co., Ltd.). The tristimulus values (L * 、a * 、b * ), using the difference in tristimulus values before and after the weathering test (ΔL * , Δa * , Δb * ), and the color difference (ΔE) was calculated using the following formula (I).
[0133] ΔE={(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 ···(I).
[0134] (5) Weathering test of fiber reinforced composite materials
[0135] The fiber direction of the prepreg produced by the above <Prepreg production method> was aligned and 20 layers were stacked. The temperature was raised from 30°C to 90°C at a speed of 1.7°C / min under a pressure of 0.7MPa in an autoclave. After being kept at 90°C for 60 minutes, the temperature was raised to 135°C at a speed of 2.0°C / min. The CFRP plate of a unidirectional material with a thickness of 2mm was produced, and a test piece with a width of 37mm and a length of 68mm was cut out. The test piece was placed in an outdoor place without a roof and without shade when the sun was out, and was placed for 2 months to conduct a weathering test. The test pieces before and after the weathering test were arranged side by side, and different opinions on the color were heard from 10 subjects. The case where more than 8 of the 10 subjects answered "no color change" or "don't know the color change" was set as "0", and the case where more than 3 subjects answered "there was a color change" was set as "×".
[0136] <Example 1>
[0137] A resin composition was prepared according to the above-mentioned <Method for preparing resin composition> using 35 parts by mass of "EPICLON (registered trademark)" N-775 as component [A], 25 parts by mass of "DER (registered trademark)" 858 as component [B], 20 parts by mass of "Denacol (registered trademark)" EX-614B as component [C], 20 parts by mass of "EPICLON (registered trademark)" 830 as other epoxy resin (component [H]), 5.8 parts by mass of DICY7 as dicyandiamide as component [D], 3 parts by mass of "Fennotot (registered trademark)" YP-70 as component [G]: a phenoxy resin, and 3 parts by mass of DCMU99 as a curing accelerator.
[0138] A cured resin was prepared from the obtained resin composition according to the <Preparation method of cured product>. The bending modulus, glass transition temperature, transparency, and weather resistance (color difference ΔE) of the cured resin were measured. The bending modulus was 4.0 GPa, the glass transition temperature was 140°C, the transparency was A, and the color difference ΔE was 6.7. The physical properties and appearance of the cured resin were good.
[0139] A prepreg was prepared from the obtained resin composition according to <Prepreg Preparation Method> and measured according to "(5) Weather resistance of fiber-reinforced composite material" in <Various Evaluation Methods>. The fiber-reinforced composite material had good weather resistance.
[0140] <Examples 2 to 14>
[0141] The cured resin and prepreg were prepared in the same manner as in Example 1 except that the composition was changed as shown in Table 1. Regarding each example, the flexural modulus, glass transition temperature, transparency, weather resistance (color difference ΔE) of the cured resin, and the weather resistance of the fiber-reinforced composite material were all good as shown in Table 1.
[0142] <Comparative Example 1>
[0143] The composition shown in Table 2 was set to produce a cured resin product and a prepreg by the same method as in Example 1. The results of the physical property evaluation are shown in Table 1 (the same in the following comparative examples). The transparency, weather resistance, and weather resistance of the cured resin product and the fiber-reinforced composite material were good. However, since the content of component [A] was less than 20 parts by mass in 100 parts by mass of the total epoxy resin, condition (1) was not satisfied, and therefore the bending modulus and glass transition temperature of the cured resin product were lower than those in Example 5.
[0144] <Comparative Example 2>
[0145] The composition shown in Table 3 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good flexural modulus, glass transition temperature, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the content of component [A] exceeded 50 parts by mass in 100 parts by mass of the total epoxy resin, which did not satisfy condition (1), so the transparency of the cured resin was poor compared to that of Example 6.
[0146] <Comparative Example 3>
[0147] The composition shown in Table 4 was used to prepare a cured resin and a prepreg in the same manner as in Example 1. The cured resin had good flexural modulus, transparency, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the content of component [B] was less than 10 parts by mass in 100 parts by mass of the total epoxy resin, which did not satisfy condition (2), and thus the glass transition temperature was lower than that of Example 8.
[0148] <Comparative Example 4>
[0149] The composition shown in Table 2 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good glass transition temperature, transparency, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the content of component [B] exceeded 40 parts by mass in 100 parts by mass of the total epoxy resin, which did not satisfy condition (2), so the flexural modulus of the cured resin was lower than that of Example 5.
[0150] <Comparative Example 5>
[0151] The composition shown in Table 2 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good glass transition temperature, transparency, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the content of component [C] was less than 10 parts by mass in 100 parts by mass of the total epoxy resin, which did not satisfy condition (3), and thus the flexural modulus was lower than that of Example 5.
[0152] <Comparative Example 6>
[0153] The composition shown in Table 4 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good flexural modulus, transparency, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the content of component [C] exceeded 40 parts by mass in 100 parts by mass of the total epoxy resin, which did not satisfy condition (3), and therefore the glass transition temperature of the cured resin was lower than that of Example 8.
[0154] <Comparative Example 7>
[0155] The composition shown in Table 3 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good flexural modulus, glass transition temperature, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the total content of component [B] and component [C] in 100 parts by mass of the total epoxy resin was less than 40 parts by mass, which did not satisfy condition (4), so the transparency of the cured resin was poor compared to that of Example 6.
[0156] <Comparative Example 8>
[0157] The composition shown in Table 4 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good flexural modulus, transparency, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the content of component [C] exceeded 40 parts by mass in 100 parts by mass of the total epoxy resin, which did not satisfy condition (3), and the content of component [A] was less than 20 parts by mass, which did not satisfy condition (1), so the glass transition temperature of the cured resin was lower than that of Example 9.
[0158] <Comparative Example 9, Comparative Example 10>
[0159] The composition shown in Table 5 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good glass transition temperature, transparency, weather resistance, and weather resistance of the fiber-reinforced composite material. However, since component [C] was not mixed and condition (3) was not satisfied, the flexural modulus was lower than that of all the examples.
[0160] <Comparative Example 11>
[0161] The composition shown in Table 5 was used to prepare a cured resin and a prepreg in the same manner as in Example 1. The cured resin had good flexural modulus, glass transition temperature, weather resistance, and weather resistance of the fiber-reinforced composite material. However, component [C] was not mixed, and condition (3) was not satisfied, so the transparency was poor compared to all the examples.
[0162] <Comparative Example 12>
[0163] The composition shown in Table 3 was used to prepare a cured resin and a prepreg in the same manner as in Example 1. The cured resin had good flexural modulus, glass transition temperature, weather resistance, and weather resistance of the fiber-reinforced composite material. However, component [C] was not mixed, but pentaerythritol-based epoxy resin (aliphatic epoxy resin having no hydroxyl group) was mixed instead, but this did not satisfy condition (3), so the transparency was poor compared to Example 6.
[0164] <Comparative Example 13>
[0165] The composition shown in Table 3 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good flexural modulus, glass transition temperature, and transparency. However, the content of component [E] exceeded 10 parts by mass in 100 parts by mass of the total epoxy resin, which did not satisfy condition (5). Therefore, the weather resistance of the cured resin and the weather resistance of the fiber-reinforced composite material were inferior to those of Examples 6 and 10.
[0166] <Comparative Example 14>
[0167] The composition shown in Table 2 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good glass transition temperature, transparency, weather resistance, and weather resistance of the fiber-reinforced composite material. However, since component [D] was not mixed, the flexural modulus of the cured resin was lower than that of Example 5.
[0168] <Comparative Example 15>
[0169] The composition shown in Table 3 was used to prepare a cured resin and a prepreg by the same method as in Example 1. The cured resin had good flexural modulus, glass transition temperature, weather resistance, and weather resistance of the fiber-reinforced composite material. However, the total content of component [B] and component [C] in 100 parts by mass of the total epoxy resin was less than 40 parts by mass, which did not satisfy condition (4), so the transparency of the cured resin was poor compared to that of Example 6.
[0170] [Table 1]
[0171]
[0172] [Table 2]
[0173] Table 2
[0174]
[0175] [Table 3]
[0176] Table 3
[0177]
[0178] [Table 4]
[0179] Table 4
[0180]
[0181] [Table 5]
[0182] Table 5
[0183]
Claims
1. A prepreg comprising reinforcing fibers and a resin composition, wherein the resin composition comprises the following components [A] to [D] and satisfies the following conditions (1) to (5), Ingredient [A]: Novolac type epoxy resin, Ingredient [B]: Oxazolidinone type epoxy resin, Component [C]: either or both of a sorbitol-based epoxy resin and a glycerin-based epoxy resin, Ingredient [D]: dicyandiamide, Condition (1): The content of component [A] is 20 to 50 parts by mass based on 100 parts by mass of the total epoxy resin. Condition (2): The content of component [B] is 10 to 40 parts by mass based on 100 parts by mass of the total epoxy resin. Condition (3): The content of component [C] is 10 to 40 parts by mass based on 100 parts by mass of the total epoxy resin. Condition (4): 40 parts by mass or more of component [B] and component [C] are contained in 100 parts by mass of the total epoxy resin. Condition (5): Component [E]: glycidylamine epoxy resin is not contained, or even if contained, the content is 10 parts by mass or less based on 100 parts by mass of the total epoxy resin. 2 . The prepreg according to claim 1 , which does not contain the component [E], or even if it contains it, the amount is 1 part by mass or less based on 100 parts by mass of the total epoxy resin. 3 . The prepreg according to claim 1 , further comprising component [F]: a compound having a boiling point of 130° C. or higher, a molecular weight m of 50 or more and 250 or less, having no epoxy group in the molecule, and having no epoxy resin curing ability. 4 . The prepreg according to claim 1 , comprising component [G]: a phenoxy resin as the thermoplastic resin. 5 . A fiber-reinforced composite material obtained by curing the prepreg according to claim 1 . 6 . A fiber-reinforced composite material tubular body, which is obtained by molding the prepreg according to claim 1 .
7. A golf club shaft, which is formed by using the fiber-reinforced composite material tubular body according to claim 6.
8. A fishing rod, which is formed by using the fiber-reinforced composite material tubular body according to claim 6.
Citation Information
Patent Citations
Epoxy resin composition and autohesive prepreg
JP2003261744A
Towpreg and production method thereof and production method of pressure vessel
JP2020158594A
Prepreg, fiber-reinforced composite resin molded body, method for producing tubular molded body, epoxy resin composition, and tubular molded body
WO2020080474A1